Physicochemical Treatment and Disposal of Hazardous Waste - Willie Doaemo; Panagiotis Karvounis (Diponegoro University, 2019)
Since massive urbanization occurs, more and more waste is produced in yearly bases; a situation that drives sanitation facilities exceeding their capacities. On top of that with increased industrialization activity significantly more hazardous waste is produced and disposed as contaminated water or hazardous solid waste. This is a problem, both developed and developing states face and it can dispute the biogeochemical cycles and has side effects in human health and environment. In this report we review in detail physicochemical properties of the hazardous chemicals released to the environment and provide an overview of the various hazardous waste treatment technologies. The goal is encourage government to implement policies to ensure water pollution is controlled and enforced by law.